100 first dinosaur words - Sirett, Dawn; Hare, Rachael (London Dorling Kindersley Limited, 2019)
Labeled pictures introduce the words for a variety of dinosaurs
Scientific Notions
1 2 23
Keywords: Dinosaurs -- Juvenile literature; Vocabulary -- Juvenile literature